Speaking for Ourselves: The Ghanaian Encounter with European Missionaries – Sixteenth–Twenty-first Centuries - Eshun, Daniel Justice (Mission studies, 2021)
This paper (re)examines European missionary encounters with Ghanaians from the sixteenth – twenty-first centuries from Ghanaian perspectives. The paper makes three main arguments: first, European missionary endeavours were quite peripheral to ongoing indigenous religious activities and daily life, with the movement of Christianity from the periphery to the center of Ghanaian society a more recent phenomenon with political implications and concerns. Secondly, missionary and colonial decisions were often made in response to indigenous activities, not vice versa. And thirdly, this methodological approach of hearing African and European voices in dialogue serves as a much-needed corrective to favouring European perspectives within African mission history. Taken together, this provides fresh insights into questions of how/why Christianity went from the periphery under European missionary leadership to Ghana’s primary religion post-independence, offering differently nuanced understandings to concepts of mission while giving dignity and respect to the local context, people, and institutions.